EFEKTIVITAS PENERAPAN SANKSI TERHADAP PELAKU PENCEMARAN LINGKUNGAN HIDUP AKIBAT SAMPAH DI KOTA PAREPARE - Asram A.T. Jadda, Sadriyah Mansur, Asrul Hidayat, Wardatul Jannah (Madani Legal Review, 2022)
Cleanliness is a key element in realizing health. In the development and management of waste becomes very important and this cannot be separated from the participation of the community in managing waste. however, at the edge of Mattirotasi Beach, it is found that there is still a behavior of people who throw garbage carelessly. The research with the title "Effectiveness of the Application of Sanctions Against Environmental Pollution Actors Due to Garbage in Parepare City", has a problem formulation how is the effectiveness of the application of sanctions against perpetrators of environmental pollution due to waste in Parepare City, and what factors affect the effectiveness of the application of sanctions against perpetrators of environmental pollution. living due to garbage in the city of Parepare. The purpose of this study is to find out how effective the application of sanctions against perpetrators of environmental pollution due to waste in the city of Parepare is, and to find out what factors affect the effectiveness of the application of sanctions against perpetrators of environmental pollution due to waste in the city of Parepare. This research uses descriptive qualitative research with an empirical normative approach. The source of the data used is to examine things that are theoretical by using secondary data, including the principles, rules, norms and legal rules contained in laws and regulations, studying books, and other documents that are closely related to this research. Based on this research, coordination between government agencies in conducting guidance, supervision, and evaluation of these regional regulations has not been synergistic and integrated, so that it becomes ineffective. The factors that hinder the government of Parepare City in applying sanctions against perpetrators of environmental pollution are legal factors, indecision by law enforcement, inadequate facilities and infrastructure, community factors that are not aware of the importance of law to be obeyed, and legal culture factors.